2012
DOI: 10.1111/j.1600-0447.2012.01839.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of people at risk of developing a first psychosis: comparison of two recruitment strategies

Abstract: The screening method detects more patients with at-risk mental states than the referral method. The latter method is biased to young male patients in an earlier prodromal stage and a lower transition rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 43 publications
(88 reference statements)
6
69
2
1
Order By: Relevance
“…In fact, preliminary data indicates that distress associated with attenuated psychotic symptoms or reason for referral being due to attenuated psychotic symptoms [5] does not correspond to higher risk for transition to psychotic disorder. The findings of Rietdijk et al [11] are consistent with this. They found that at-risk patients ascertained via a traditional case-recruitment strategy, relying on referral when psychotic symptoms were suspected, resulted in lower transition rates to psychosis than sequential screening of a help-seeking population entering secondary mental health services for non-psychotic problems.…”
Section: Distress Associated With Apssupporting
confidence: 82%
“…In fact, preliminary data indicates that distress associated with attenuated psychotic symptoms or reason for referral being due to attenuated psychotic symptoms [5] does not correspond to higher risk for transition to psychotic disorder. The findings of Rietdijk et al [11] are consistent with this. They found that at-risk patients ascertained via a traditional case-recruitment strategy, relying on referral when psychotic symptoms were suspected, resulted in lower transition rates to psychosis than sequential screening of a help-seeking population entering secondary mental health services for non-psychotic problems.…”
Section: Distress Associated With Apssupporting
confidence: 82%
“…Consequently, had they been used as a screener as suggested by several studies [36,37,38], simple-rated PLEs would have been highly sensitive but far too unspecific, as they would have detected nearly everyone with mental problems presenting at the early detection center, including those without any mental disorder. The specificity of PLEs might have been higher at higher thresholds, but most likely at the cost of sensitivity, as reported in a study evaluating the CAPE as a screening instrument for at-risk states according to the Comprehensive Assessment of At-Risk Mental States [36].…”
Section: Discussionmentioning
confidence: 99%
“…Only 6.9% of this subsample reported distress associated with their attenuated psychotic symptoms (Kelleher et al, 2012). Other studies that explored screening strategies for detection of people at risk of developing psychosis found higher rates of transition to psychotic disorder in young people meeting UHR criteria who were seeking help for general (non-psychotic) psychiatric problems than in a UHR group referred to specialized services for psychosis Rietdijk et al, 2012). The distress associated with the APS in the former group was presumably lower than in the latter group, because these symptoms were only detected via screening and were not necessarily a significant source of distress or reason for help-seeking/referral.…”
Section: Introductionmentioning
confidence: 96%
“…Based on the clinical observations noted above it was hypothesised that the main source of clinical distress experienced by UHR patients would be non-specific psychopathology rather than APS. We also hypothesised, based on previous findings Rietdijk et al, 2012), that the level of distress associated with those non-psychosis related symptoms would be more predictive of transition to psychosis than distress associated to APS alone.…”
Section: Introductionmentioning
confidence: 99%